Quality Assessment and Comparative Analysis of Malinau Coffee Among Indonesian Specialty Coffees - Adi Sutrisno; Etty Wahyuni; Dwi Santoso; Mohammad Wahyu Agang; Deny Titing; Erwan Kusnadi; Tjahjo Tri Hartono; Mas Davino Sayaza; Elida Novita; Rahmat Pramulya; Devi Maulida Rahmah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Malinau Robusta coffee demonstrates untapped potential within the specialty coffee market. This study aims to evaluate the quality of Malinau coffee comprehensively and benchmark it against prominent specialty coffees such as Gayo, Toraja, and Kintamani. A descriptive quantitative method was employed to analyze critical parameters including caffeine content, moisture level, defect value, impurity level, grain size, and flavor profile. Coffee samples were gained from nine coffee-producing villages in Malinau Regency, involving 28 farmers covering 190 ha of coffee plantations. The results identified distinct strengths of Malinau coffee, notably its low moisture level (10.2%) and high caffeine content (1.94%) among the samples, offering a strong and intense flavor profile including chocolatey, a bitter aftertaste, and fruity undertones. Challenges for Malinau coffee includes high defect value (65.7/300 g) and impurity level (0.6%), which undermine its marketability in premium segments. To bring Malinau coffee up to par with other established specialty coffees, improvements in post harvest handling are needed, particularly sorting, quality control and consistent processes methods. By adopting innovative cultivation and processing, Malinau coffee holds strong potential as a competitor of specialty coffee, both for domestic and global markets while highlighting its unique regional identity. Keywords: Malinau coffee, North Kalimantan, Quality improvement, Robusta, Specialty coffee.